Estimating the balance sheet of the personal sector in an emerging market country: South Africa 1975 - 2003 - Janine Aron; John Muellbauer; Johan Prinsloo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Official balance sheet estimates for the household sector are not currently available in South Africa, yet, with the country's well developed financial sector and deep capital markets, asset market channels are likely to be important determinants of aggregate consumer spending and saving, consumer demand for credit and their broad money holdings. The current paper aims to produce comprehensive estimates of household balance sheets for South Africa. The paper draws, where feasible, on best practice from the Office of National Statistics of the UK and assesses the quality of the data sources and suggests areas where additional surveys or improvements in data collection procedures would be helpful to further improve the quality of the balance sheet estimates. Furthermore, quarterly balance sheet measures to 2003 are provided, and linked to quarterly measures. The main balance sheet categories are liquid assets, household debt and various categories of illiquid financial and tangible assets, including pension wealth, directly held shares and bonds, and housing. Revised debt estimates and new estimates of tangible assets for households and unincorporated businesses are provided. The paper describes the trends of the estimates of the household sector's balance sheets and of total net wealth. The paucity of data for developing and emerging market countries is illustrated by means of a survey, and lessons are drawn from the South African research for the compilation of household sector balance sheets.
Keywords: E0; E1; E21; 330; emerging market countries; household sector wealth; South Africa; Haushaltsbudget-Statistik; Südafrika